2014
DOI: 10.1021/jp502853b
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition and Enantioselective Photoelectrochemical Oxidation toward Amino Acids on Single-Crystalline ZnO

Abstract: A novel chiral photoanode was fabricated by in situ constructing surface molecular imprinting (MI) sites on vertically aligned single-crystalline (SC) ZnO, employing the l- or d-amino acid enantiomer as templates. The photoelectrochemical (PEC) experiments showed that the photoanode exhibited chiral recognition and enantioselective PEC oxidation ability to the template enantiomer, compared with the other one. The photocurrent response of l-Phe on the l-SC photoanode was 4.8 times the value of d-Phe. A similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The complexes of template and catalyst precursors are then polymerized to the raw materials in the presence of cross-linkers. The subsequent removal of the templates leaves specific cavities complementary to the shape, size, or specific groups of the template molecules, offering an efficient approach to enrich target molecules on the surface for further oxidation. , A series of catalysts with high activity and selectivity has been reported for water decontamination. ,, Zhao’s group has been devoted to the development of various molecular imprinting catalysts for selective photoelectrochemical oxidation of nonbiodegradable toxic micropollutants. ,,,, For example, bisphenol A-imprinted n-P heterojunction TiO 2 nanoelectrode catalyzed the degradation of 20 mg L –1 bisphenol A with a pseudo first-order rate constant of 1.76 h –1 , 3.7 times higher than that in the nonmolecularly imprinted system. Moreover, high selectivity toward bisphenol A in the presence of 2-naphthol with similar structure and higher concentration (50 mg L –1 ) was observed …”
Section: Selective Oxidation Via Tuning the Accessibility Of Targets ...mentioning
confidence: 99%
“…The complexes of template and catalyst precursors are then polymerized to the raw materials in the presence of cross-linkers. The subsequent removal of the templates leaves specific cavities complementary to the shape, size, or specific groups of the template molecules, offering an efficient approach to enrich target molecules on the surface for further oxidation. , A series of catalysts with high activity and selectivity has been reported for water decontamination. ,, Zhao’s group has been devoted to the development of various molecular imprinting catalysts for selective photoelectrochemical oxidation of nonbiodegradable toxic micropollutants. ,,,, For example, bisphenol A-imprinted n-P heterojunction TiO 2 nanoelectrode catalyzed the degradation of 20 mg L –1 bisphenol A with a pseudo first-order rate constant of 1.76 h –1 , 3.7 times higher than that in the nonmolecularly imprinted system. Moreover, high selectivity toward bisphenol A in the presence of 2-naphthol with similar structure and higher concentration (50 mg L –1 ) was observed …”
Section: Selective Oxidation Via Tuning the Accessibility Of Targets ...mentioning
confidence: 99%
“…Chirality plays a crucial effect in chemical recognition and interactions between chemical and biological species, relating to many application fields including chiral recognition, chiral catalysis, and chiral bio-nanoscience. Chiral nanostructures have shown great potential and a promising future for sensing, cytotoxicity mediation and cell imaging, , asymmetric catalysis and enantiomeric separation, ,, circularly polarized light sources, and spintronics. In 1998, Schaaff et al first reported the chiral nanoparticles, stabilizing chiral glutathione to gold nanoclusters . However, the study on the fabrication and properties of chiral nanostructures is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Several concepts have been tested in the past such as the binding of chiral ligands to metal surfaces 32 , the adsorption of chiral molecules on surfaces to produce chiral metals 33 , or metal oxides 34 , 35 , the cutting of high Miller index planes of metal monocrystals 36 , 37 , and the distortion of symmetrical metal structures 38 . The design and synthesis of chiral metal structures has been explored for several of them (e.g., Pt, Pd, Ag, Au, Cu, Rh) 39 44 .…”
Section: Introductionmentioning
confidence: 99%